Environment-friendly antistatic LED-UV (Light Emitting Diode-Ultraviolet) curing ink functional agent
By using composite conductive nanomaterials in the ink, combined with carbon nanotubes and polyacetylene iodized, the problem of reducing ink adhesion caused by electrostatic accumulation is solved, and higher printing quality and scratch resistance are achieved.
Patent Information
- Application Number
- CN202411569960.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-06
AI Technical Summary
During a long printing process, electrostatic accumulation leads to a decrease in ink adhesion, which is not resistant to scratches after curing, and blurred layers, affecting printing quality.
The composite conductive nanomaterial is used to form a structure that derives charge through the combination of carbon nanotubes and polyacetylene iodized, which enhances the charge derivation flow ability, and improves the fluidity and suspension effect of the ink through the addition of silicone oil and surfactant.
Effectively maintain the ability to carry charge, avoid uneven coating of ink due to charge, enhance the printing quality of the layer, and improve the adhesion and scratch resistance of the ink.
Smart Images

Figure CN119463585A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ink additives, and in particular to an environmentally friendly antistatic LED-UV curing ink functional agent. Background Art
[0002] LED-UV ink is an ink that cures instantly after being irradiated with light of 395nm wavelength. It includes photoinitiator, monomer, diluent, thickener and auxiliary additives. The light energy is absorbed by the photoinitiator in the ink to produce active fragments, which polymerize oligomers or monomers containing double bonds to form a cross-linked network, and finally realize the curing of the ink. However, due to the printing substrate, during the rapid printing process, the rapid rotation and movement of the printing substrate causes friction electrification, which generates a large amount of static electricity on the surface of the substrate. When the UV ink is transferred to the surface of the substrate by roller coating, the existence of electric charge causes the ink and the substrate to repel each other, resulting in roller slippage and uneven roller coating. After the ink molecules are charged, not only will the adhesion between the ink and the substrate be small during the curing process, but the ink will also be unevenly distributed on the surface of the substrate, resulting in white leakage.
[0003] The existing solution to the problem of static electricity is mainly to add antistatic agents to the ink, such as using substances containing ether bonds such as polyoxyethylene castor oil, polyoxyethylene laurate, and polyethylene glycol to form a conductive channel after combining with water to guide excess charge and reduce static electricity. However, the antistatic agent of this method is unevenly distributed in the resin. Excessive use will cause low ink adhesion and scratch resistance, and will also cause oily substances to ooze out of the paint film surface, reducing the appearance of the packaging material. Another method is to treat the surface of the substrate with a surfactant before curing, increase adhesion through the lipophilic group on the substrate surface, and combine the hydrophilic group with water to form a conductive layer, thereby guiding the surface charge of the substrate to eliminate the influence of static electricity. However, this method cannot remove the static electricity carried by the UV ink itself very well. After long-term printing, the charge accumulates in the ink storage box, resulting in the occurrence of ink flying, causing the printed image to be blurred and the printing quality to decline. Summary of the invention
[0004] In order to solve the problem of static electricity accumulation during long-term printing, excessive addition of antistatic agent to UV ink to counteract a large amount of static electricity leads to reduced ink adhesion, which causes the ink to be scratch-resistant after curing, and the printed layer to be blurred and the picture quality to be reduced, the present invention provides an environmentally friendly antistatic LED-UV curing ink functional agent, including the following specific components: The following specific ingredients are composed by weight: Composite conductive nanomaterial: 10-30 parts, resin: 6-12 parts, silicone oil: 20-40 parts, surfactant: 1-5 parts and water: 10-20 parts.
[0005] The composite conductive nanomaterial is prepared by filling carbon nanotubes and iodinated polyacetylene in a weight ratio of 1:1-1.2 and then stabilizing the mixture.
[0006] The preparation method of the composite conductive nanomaterial is as follows: S1. Treat the carbon nanotubes with concentrated nitric acid and dry them, then perform plasma etching to obtain uncapped carbon nanotubes. Place the uncapped carbon nanotubes in water and treat them under pressure and at elevated temperatures. After surface drying, obtain carbon nanotubes, the inner diameter of which is 20-50 nm.
[0007] S2. Place polyacetylene in iodine vapor for reaction to obtain iodinated polyacetylene.
[0008] S3, self-assembly of iodinated polyacetylene and carbon nanotubes, dissolving iodinated polyacetylene in a solvent, adding a surfactant, then adding carbon nanotubes and stirring for reaction, and after evaporating the solvent, obtaining composite conductive nanotubes.
[0009] S4. placing the composite conductive nanotubes in chloroform, adding iron powder for ultrasonic mixing treatment, and then obtaining a stabilized composite conductive nanomaterial through thermal reaction.
[0010] The technical solution adopted in the present application not only uses a surfactant, but also adopts a composite conductive nanomaterial with better charge extraction performance, and uses iodinated polyacetylene to cooperate with carbon nanotubes to enhance the ability of charge extraction and flow. In the face of a large amount of charge accumulation, the ability to carry charge can be effectively maintained. Filling iodinated polyacetylene into carbon nanotubes can slow down the disappearance of the polyacetylene π electron cloud and avoid the loss of conjugated structure. Therefore, this functional agent can produce strong conductivity during the ink roller coating process and the ultraviolet light curing process, avoid uneven application of ink due to charge, and enhance the printing quality of the layer.
[0011] The iodinated polyacetylene and carbon nanotubes used in the present application are filled in a weight ratio of 1-1.2:1, which can effectively make part of the molecular chains of polyacetylene located outside the carbon nanotubes. Since such external polyacetylene molecular chains have carbon-carbon double bonds, they can be effectively connected with the resin monomer and the cross-linking curing agent to form a strong grid structure, thereby enhancing the adhesion to the surface of the substrate, and will not affect the conjugated structure of the remaining polyacetylene chains in the carbon nanotubes, thereby maintaining a strong antistatic ability.
[0012] The present application also uses silicone oil in the functional agent. The addition of silicone oil reduces the viscosity of the ink and increases the fluidity of the UV ink, so that the composite conductive nanomaterial in the functional agent can obtain a better suspension effect. After being added to the ink, it can be dispersed more evenly, thereby enhancing the overall resistance of the ink to electric charge and achieving better printing effect.
[0013] Furthermore, the carbon nanotubes in S1 are multi-walled carbon nanotubes, the diameter of the multi-walled carbon nanotubes is 30-80nm, the ratio of the carbon nanotubes to water is 1:2, the treatment pressure is 1.5-3.0MPa, the treatment temperature is 140-220°C, and the pressurized and heated treatment is followed by ultrasonic treatment, the ultrasonic power is 200-300w, and the ultrasonic treatment time is 20-30min.
[0014] The present application uses multi-walled carbon nanotubes, which have the advantage of a larger inner diameter than single-walled carbon nanotubes, making it easier for polyacetylene to pass through, and uses high-pressure treatment to form water clusters inside the carbon nanotubes, making it easier for polyacetylene to fill into the carbon nanotubes.
[0015] Furthermore, the S3 solvent is one of n-octane, chloroform, chloroform or tetrahydrofuran, and the solid-liquid ratio of the iodinated polyacetylene to the solvent is 1g:100-120ml.
[0016] Furthermore, the surfactant in S3 is one of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium tetrapropylene benzene sulfonate or sodium diisooctyl sulfosuccinate.
[0017] The present application adds a small amount of surfactant to allow better contact between the carbon nanotubes and the iodinated polyacetylene, thereby promoting the filling of the polyacetylene structure.
[0018] Furthermore, the added volume ratio of the surfactant to the solvent in S3 is 2-10:100.
[0019] Furthermore, the solid-liquid ratio of the carbon nanotubes in S1 treated with concentrated nitric acid is 1g:10ml, the treatment temperature is 140-200°C, and the reaction time is 24-48h.
[0020] Furthermore, the plasma excitation power of the plasma etching in S1 is 100-2000W, the etching environment pressure is 1000Pa, and the impact gas of the plasma etching is one of oxygen, air, nitrogen or argon.
[0021] Furthermore, the usage amount of the functional agent is 3-15% of the LED-UV curing ink.
[0022] The environmentally friendly antistatic LED-UV curing ink functional agent prepared by the invention can be applied in relevant inks.
[0023] This application has at least the following beneficial effects: 1. In the process of preparing the functional agent for curing ink, the present application uses multi-walled carbon nanotubes and polyacetylene to form a structure for exporting charges. This structure not only has good conductivity and avoids charge accumulation, but also can increase the degree of cross-linking, enhance the connection strength between the functional agent and the ink, and indirectly enhance the adhesion between the ink and the substrate, making it more scratch-resistant.
[0024] 2. The present application uses plasma etching to open a certain gap on the surface or end of the carbon nanotube to facilitate the filling of polyacetylene into the carbon nanotube. After the polyacetylene is filled into the carbon nanotube, the filled carbon nanotube is treated with chloroform and iron powder to facilitate the removal of polyacetylene or other impurities on the outer wall of the carbon nanotube that are not fixedly connected, thereby reducing the oxygen barrier distance, making the effective composite conductive nanomaterial more pure, and enhancing the connection strength between the polyacetylene inside the carbon nanotube and the inner wall of the carbon nanotube through thermal reaction. Therefore, after being added to the UV ink, it can maintain a strong ability to export charges, and remove charges through the water layer in the functional agent, thereby enhancing the uniformity of the ink pattern, forming a more regular layer, and enhancing the printing effect.
[0025] 3. The functional agent of the present application is not only antistatic before curing and reduces the surface tension of the ink, but also maintains a strong ability to prevent static electricity accumulation after curing and forming a film, avoiding the adsorption of dust. The carbon nanotubes effectively protect the conjugated structure of polyacetylene. Compared with the unprotected polyacetylene, the double bonds are opened and cross-linked during curing. The polyacetylene protected by the carbon nanotubes will not cross-link with the photoinitiator and the resin monomer inside the carbon nanotubes, and can protect the film layer for a long time. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the resistivity of the surface of UV ink films of various embodiments of the present invention and various comparative examples at different addition ratios. DETAILED DESCRIPTION
[0027] The following will refer to the attached Figure 1 The embodiments of the present invention are described in detail. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.
[0028] Preparation Example 1 Preparation of composite conductive nanomaterials, the specific preparation steps are as follows: S1. By weight, 10 parts of multi-walled carbon nanotubes are immersed in 100 parts of concentrated nitric acid at a temperature of 180°C for 24 hours, and then washed with water, heated and dried, and then placed in an etching chamber for plasma etching. The working gas for plasma etching is air, the plasma excitation power is 1000W, and the etching environment pressure is 1000Pa to obtain uncapped carbon nanotubes. The uncapped carbon nanotubes are placed in 20 parts of water, pressurized to 2.0MPa, heated to 180°C, and then ultrasonically treated with an ultrasonic power of 300W for 25min. After surface drying, carbon nanotubes are obtained, and the inner diameter of the carbon nanotubes is 30-50nm.
[0029] S2. 11 parts of polyacetylene are placed on a mesh in a reactor, and iodine vapor is input into the lower part of the reactor for reaction. The mass ratio of polyacetylene to iodine vapor is 1:2.5, and the reaction temperature is 200° C. to obtain iodinated polyacetylene.
[0030] S3. Dissolve iodinated polyacetylene in n-octane with a solid-liquid ratio of iodinated polyacetylene to n-octane of 1 g:110 ml, add sodium dodecyl sulfate in a volume that is 5% of the volume of n-octane, add carbon nanotubes thereto, stir and react, heat and evaporate the n-octane to obtain composite conductive nanotubes.
[0031] S4. Place the composite conductive nanotubes in chloroform, add iron powder for ultrasonic mixing treatment, the ultrasonic treatment power is 120W, the amount of iron powder added is 10% of the weight of the composite conductive nanotubes, heat the chloroform to react for 20 minutes, and obtain a stabilized composite conductive nanomaterial.
[0032] Preparation Example 2 Preparation of composite conductive nanomaterials, the specific preparation steps are as follows: S1. By weight, 10 parts of multi-walled carbon nanotubes are immersed in 100 parts of concentrated nitric acid at a temperature of 140°C for 24 hours, and then washed with water, heated and dried, and then placed in an etching chamber for plasma etching. The working gas for plasma etching is oxygen, the plasma excitation power is 100W, and the etching environment pressure is 1000Pa to obtain uncapped carbon nanotubes. The uncapped carbon nanotubes are placed in 20 parts of water, pressurized to 1.5MPa, heated to 140°C, and then ultrasonically treated with an ultrasonic power of 200W for 20min. After surface drying, carbon nanotubes are obtained, and the inner diameter of the carbon nanotubes is 20-40nm.
[0033] S2. 10 parts of polyacetylene are placed on a mesh in a reactor, and iodine vapor is input into the lower part of the reactor for reaction. The mass ratio of polyacetylene to iodine vapor is 1:2, and the reaction temperature is 190°C to obtain iodinated polyacetylene.
[0034] S3. Dissolve iodinated polyacetylene in chloroform with a solid-liquid ratio of iodinated polyacetylene to chloroform of 1 g:100 ml, add sodium dodecyl sulfate in a volume that is 2% of the volume of chloroform, add carbon nanotubes thereto, stir and react, heat and evaporate the chloroform, and obtain composite conductive nanotubes.
[0035] S4. Place the composite conductive nanotubes in chloroform, add iron powder for ultrasonic mixing treatment, the ultrasonic treatment power is 120W, the amount of iron powder added is 10% of the weight of the composite conductive nanotubes, heat the chloroform to react for 20 minutes, and obtain a stabilized composite conductive nanomaterial.
[0036] Preparation Example 3 Preparation of composite conductive nanomaterials, the specific preparation steps are as follows: S1. By weight, 10 parts of multi-walled carbon nanotubes are immersed in 100 parts of concentrated nitric acid at a temperature of 200°C and a reaction time of 48 hours. The tubes are washed with water, heated and dried, and then placed in an etching chamber for plasma etching. The working gas for plasma etching is nitrogen, the plasma excitation power is 2000W, and the etching environment pressure is 1000Pa to obtain uncapped carbon nanotubes. The uncapped carbon nanotubes are placed in 20 parts of water, pressurized to 13.0MPa, heated to 220°C, and then ultrasonically treated at a power of 300W for 30 minutes. After surface drying, carbon nanotubes are obtained, and the inner diameter of the carbon nanotubes is 30-50nm.
[0037] S2. 12 parts of polyacetylene are placed on a mesh in a reactor, and iodine vapor is input into the lower part of the reactor for reaction. The mass ratio of polyacetylene to iodine vapor is 1:3, and the reaction temperature is 220° C. to obtain iodinated polyacetylene.
[0038] S3. Dissolve iodinated polyacetylene in tetrahydrofuran with a solid-liquid ratio of iodinated polyacetylene to tetrahydrofuran of 1 g:120 ml, add sodium diisooctyl sulfosuccinate in a volume of 10% of tetrahydrofuran, add carbon nanotubes thereto and stir to react, heat and evaporate the tetrahydrofuran to obtain composite conductive nanotubes.
[0039] S4. Place the composite conductive nanotubes in chloroform, add iron powder for ultrasonic mixing treatment, the ultrasonic treatment power is 120W, the amount of iron powder added is 10% of the weight of the composite conductive nanotubes, heat the chloroform to react for 20 minutes, and obtain a stabilized composite conductive nanomaterial.
[0040] Preparation Example 4 Preparation of composite conductive nanomaterials, the specific preparation steps are as follows: S1. By weight, 10 parts of multi-walled carbon nanotubes are immersed in 100 parts of concentrated nitric acid at a temperature of 160°C for a reaction time of 32 hours, and then washed with water, heated and dried, and then placed in an etching chamber for plasma etching. The working gas for plasma etching is argon, the plasma excitation power is 1400W, and the etching environment pressure is 1000Pa to obtain uncapped carbon nanotubes. The uncapped carbon nanotubes are placed in 20 parts of water, pressurized to 2.3MPa, heated to 160°C, and then ultrasonically treated with an ultrasonic power of 240W and an ultrasonic treatment time of 240min. After surface drying, carbon nanotubes are obtained, and the inner diameter of the carbon nanotubes is 30-50nm.
[0041] S2. 12 parts of polyacetylene are placed on a mesh in a reactor, and iodine vapor is input into the lower part of the reactor for reaction. The mass ratio of polyacetylene to iodine vapor is 1:2.6, and the reaction temperature is 210° C. to obtain iodinated polyacetylene.
[0042] S3. Dissolve iodinated polyacetylene in chloroform with a solid-liquid ratio of iodinated polyacetylene to chloroform being 1 g:110 ml, and add 3% volume of sodium tetrapropylene benzene sulfonate to the solution, then add carbon nanotubes to the mixture and stir to react, heat to evaporate the chloroform, and obtain composite conductive nanotubes.
[0043] S4. Place the composite conductive nanotubes in chloroform, add iron powder for ultrasonic mixing treatment, the ultrasonic treatment power is 120W, the amount of iron powder added is 10% of the weight of the composite conductive nanotubes, heat the chloroform to react for 20 minutes, and obtain a stabilized composite conductive nanomaterial.
[0044] Preparation Example 5: No plasma etching Preparation of composite conductive nanomaterials, the specific preparation steps are as follows: S1. By weight, 10 parts of multi-walled carbon nanotubes are immersed in 100 parts of concentrated nitric acid at a temperature of 180°C for 24 hours, washed with water, heated and dried, then placed in 20 parts of water, pressurized to 2.0 MPa, heated to 180°C, and then ultrasonically treated at a power of 300W for 25 minutes. After surface drying, carbon nanotubes are obtained, and the inner diameter of the carbon nanotubes is 30-50nm.
[0045] S2. 11 parts of polyacetylene are placed on a mesh in a reactor, and iodine vapor is input into the lower part of the reactor for reaction. The mass ratio of polyacetylene to iodine vapor is 1:2.5, and the reaction temperature is 200° C. to obtain iodinated polyacetylene.
[0046] S3. Dissolve iodinated polyacetylene in n-octane with a solid-liquid ratio of iodinated polyacetylene to n-octane of 1 g:110 ml, add sodium dodecyl sulfate in a volume that is 5% of the volume of n-octane, add carbon nanotubes thereto, stir and react, heat and evaporate the n-octane to obtain composite conductive nanotubes.
[0047] S4. Place the composite conductive nanotubes in chloroform, add iron powder for ultrasonic mixing treatment, the ultrasonic treatment power is 120W, the amount of iron powder added is 10% of the weight of the composite conductive nanotubes, heat the chloroform to react for 20 minutes, and obtain a stabilized composite conductive nanomaterial.
[0048] Preparation Example 6: No pressurization, heating, and ultrasonic treatment Preparation of composite conductive nanomaterials, the specific preparation steps are as follows: S1. By weight, 10 parts of multi-walled carbon nanotubes are immersed in 100 parts of concentrated nitric acid at a treatment temperature of 180°C for 24 hours, and then washed with water, heated and dried, and then placed in an etching chamber for plasma etching. The working gas for plasma etching is air, the plasma excitation power is 1000W, and the etching environment pressure is 1000Pa to obtain uncapped carbon nanotubes with an inner diameter of 30-50nm.
[0049] S2. 11 parts of polyacetylene are placed on a mesh in a reactor, and iodine vapor is input into the lower part of the reactor for reaction. The mass ratio of polyacetylene to iodine vapor is 1:2.5, and the reaction temperature is 200° C. to obtain iodinated polyacetylene.
[0050] S3. Dissolve iodinated polyacetylene in n-octane with a solid-liquid ratio of iodinated polyacetylene to n-octane of 1 g:110 ml, add sodium dodecyl sulfate in a volume that is 5% of the volume of n-octane, add carbon nanotubes thereto, stir and react, heat and evaporate the n-octane to obtain composite conductive nanotubes.
[0051] S4. Place the composite conductive nanotubes in chloroform, add iron powder for ultrasonic mixing treatment, the ultrasonic treatment power is 120W, the amount of iron powder added is 10% of the weight of the composite conductive nanotubes, heat the chloroform to react for 20 minutes, and obtain a stabilized composite conductive nanomaterial.
[0052] Preparation Example 7: The amount of iodinated polyacetylene used is less than that of carbon nanotubes Preparation of composite conductive nanomaterials, the specific preparation steps are as follows: S1. By weight, 10 parts of multi-walled carbon nanotubes are immersed in 100 parts of concentrated nitric acid at a temperature of 180°C for 24 hours, and then washed with water, heated and dried, and then placed in an etching chamber for plasma etching. The working gas for plasma etching is air, the plasma excitation power is 1000W, and the etching environment pressure is 1000Pa to obtain uncapped carbon nanotubes. The uncapped carbon nanotubes are placed in 20 parts of water, pressurized to 2.0MPa, heated to 180°C, and then ultrasonically treated with an ultrasonic power of 300W for 25min. After surface drying, carbon nanotubes are obtained, and the inner diameter of the carbon nanotubes is 30-50nm.
[0053] S2. 8 parts of polyacetylene are placed on a mesh in a reactor, and iodine vapor is input into the lower part of the reactor for reaction. The mass ratio of polyacetylene to iodine vapor is 1:2.5, and the reaction temperature is 200° C. to obtain iodinated polyacetylene.
[0054] S3. Dissolve iodinated polyacetylene in n-octane with a solid-liquid ratio of iodinated polyacetylene to n-octane of 1 g:110 ml, add sodium dodecyl sulfate in a volume that is 5% of the volume of n-octane, add carbon nanotubes thereto, stir and react, heat and evaporate the n-octane to obtain composite conductive nanotubes.
[0055] S4. Place the composite conductive nanotubes in chloroform, add iron powder for ultrasonic mixing treatment, the ultrasonic treatment power is 120W, the amount of iron powder added is 10% of the weight of the composite conductive nanotubes, heat the chloroform to react for 20 minutes, and obtain a stabilized composite conductive nanomaterial.
[0056] Preparation Example 8: Using single-walled carbon nanotubes Preparation of composite conductive nanomaterials, the specific preparation steps are as follows: S1. By weight, 10 parts of single-arm carbon nanotubes are immersed in 100 parts of concentrated nitric acid at a treatment temperature of 180°C and a reaction time of 24 hours. The carbon nanotubes are washed with water, heated and dried, and then placed in an etching chamber for plasma etching. The working gas for plasma etching is air, the plasma excitation power is 1000W, and the etching environment pressure is 1000Pa to obtain uncapped carbon nanotubes. The uncapped carbon nanotubes are placed in 20 parts of water, pressurized to 2.0MPa, heated to 180°C, and then ultrasonically treated at a power of 300W for 25 minutes. After surface drying, carbon nanotubes are obtained, and the inner diameter of the carbon nanotubes is 0.5-5nm.
[0057] S2. 11 parts of polyacetylene are placed on a mesh in a reactor, and iodine vapor is input into the lower part of the reactor for reaction. The mass ratio of polyacetylene to iodine vapor is 1:2.5, and the reaction temperature is 200° C. to obtain iodinated polyacetylene.
[0058] S3. Dissolve iodinated polyacetylene in n-octane with a solid-liquid ratio of iodinated polyacetylene to n-octane of 1 g:110 ml, add sodium dodecyl sulfate in a volume that is 5% of the volume of n-octane, add carbon nanotubes thereto, stir and react, heat and evaporate the n-octane to obtain composite conductive nanotubes.
[0059] S4. Place the composite conductive nanotubes in chloroform, add iron powder for ultrasonic mixing treatment, the ultrasonic treatment power is 120W, the amount of iron powder added is 10% of the weight of the composite conductive nanotubes, heat the chloroform to react for 20 minutes, and obtain a stabilized composite conductive nanomaterial.
[0060] Preparation Example 9: Polyacetylene without iodination Preparation of composite conductive nanomaterials, the specific preparation steps are as follows: S1. By weight, 10 parts of multi-walled carbon nanotubes are immersed in 100 parts of concentrated nitric acid at a temperature of 180°C for 24 hours, and then washed with water, heated and dried, and then placed in an etching chamber for plasma etching. The working gas for plasma etching is air, the plasma excitation power is 1000W, and the etching environment pressure is 1000Pa to obtain uncapped carbon nanotubes. The uncapped carbon nanotubes are placed in 20 parts of water, pressurized to 2.0MPa, heated to 180°C, and then ultrasonically treated with an ultrasonic power of 300W for 25min. After surface drying, carbon nanotubes are obtained, and the inner diameter of the carbon nanotubes is 30-50nm.
[0061] S2. Dissolve 11 parts of polyacetylene in n-octane with a solid-liquid ratio of polyacetylene to n-octane of 1g:110ml, and add sodium dodecyl sulfate with a volume of 5% of the volume of n-octane, then add carbon nanotubes and stir to react, heat and evaporate the n-octane to obtain composite conductive nanotubes.
[0062] S3. Place the composite conductive nanotubes in chloroform, add iron powder for ultrasonic mixing treatment, the ultrasonic treatment power is 120W, the amount of iron powder added is 10% of the weight of the composite conductive nanotubes, heat the chloroform to react for 20 minutes, and obtain a stabilized composite conductive nanomaterial. Example 1
[0063] A preparation method of an environmentally friendly antistatic LED-UV curing ink functional agent, the specific steps are as follows: Weigh 20 parts of the composite conductive nanomaterial in Preparation Example 1, 8 parts of acrylic resin, 30 parts of silicone oil, 3 parts of surfactant polyethylene glycol and 15 parts of water, place the composite conductive nanomaterial in the silicone oil, add the surfactant and the resin, stir slowly, add water during the stirring process, and mix well to obtain a curing ink functional agent. Example 2
[0064] A preparation method of an environmentally friendly antistatic LED-UV curing ink functional agent, the specific steps are as follows: Weigh 10 parts of the composite conductive nanomaterial in Preparation Example 2, 10 parts of acrylic resin, 20 parts of silicone oil, 1 part of surfactant polyethylene glycol, and 10 parts of water, place the composite conductive nanomaterial in the silicone oil, add the surfactant and the resin, stir slowly, add water during the stirring process, and mix well to obtain a curing ink functional agent. Example 3
[0065] A preparation method of an environmentally friendly antistatic LED-UV curing ink functional agent, the specific steps are as follows: Weigh 30 parts of the composite conductive nanomaterial in Preparation Example 3, 6 parts of acrylic resin, 40 parts of silicone oil, 5 parts of surfactant polyethylene glycol and 20 parts of water, place the composite conductive nanomaterial in the silicone oil, add the surfactant and the resin, stir slowly, add water during the stirring process, and mix well to obtain a curing ink functional agent. Example 4
[0066] A preparation method of an environmentally friendly antistatic LED-UV curing ink functional agent, the specific steps are as follows: Weigh 20 parts of the composite conductive nanomaterial in Preparation Example 4, 12 parts of acrylic resin, 30 parts of silicone oil, 3 parts of surfactant polyethylene glycol and 12 parts of water, place the composite conductive nanomaterial in the silicone oil, add the surfactant and the resin, stir slowly, add water during the stirring process, and mix well to obtain a curing ink functional agent.
[0067] Comparative Example 1 A preparation method of an environmentally friendly antistatic LED-UV curing ink functional agent, the specific steps are as follows: Weigh 20 parts of the composite conductive nanomaterial in Preparation Example 5, 12 parts of acrylic resin, 30 parts of silicone oil, 3 parts of surfactant polyethylene glycol and 12 parts of water, place the composite conductive nanomaterial in the silicone oil, add the surfactant and the resin, stir slowly, add water during the stirring process, and mix well to obtain a curing ink functional agent.
[0068] Comparative Example 2 A preparation method of an environmentally friendly antistatic LED-UV curing ink functional agent, the specific steps are as follows: Weigh 20 parts of the composite conductive nanomaterial in Preparation Example 6, 12 parts of acrylic resin, 30 parts of silicone oil, 3 parts of surfactant polyethylene glycol and 12 parts of water, place the composite conductive nanomaterial in the silicone oil, add the surfactant and resin, stir slowly, add water during the stirring process, and mix well to obtain a curing ink functional agent.
[0069] Comparative Example 3 A preparation method of an environmentally friendly antistatic LED-UV curing ink functional agent, the specific steps are as follows: Weigh 20 parts of the composite conductive nanomaterial in Preparation Example 7, 12 parts of acrylic resin, 30 parts of silicone oil, 3 parts of surfactant polyethylene glycol and 12 parts of water, place the composite conductive nanomaterial in the silicone oil, add the surfactant and the resin, stir slowly, add water during the stirring process, and mix well to obtain a curing ink functional agent.
[0070] Comparative Example 4 A preparation method of an environmentally friendly antistatic LED-UV curing ink functional agent, the specific steps are as follows: Weigh 20 parts of the composite conductive nanomaterial in Preparation Example 8, 12 parts of acrylic resin, 30 parts of silicone oil, 3 parts of surfactant polyethylene glycol and 12 parts of water, place the composite conductive nanomaterial in the silicone oil, add the surfactant and the resin, stir slowly, add water during the stirring process, and mix well to obtain a curing ink functional agent.
[0071] Comparative Example 5 A preparation method of an environmentally friendly antistatic LED-UV curing ink functional agent, the specific steps are as follows: Weigh 20 parts of the composite conductive nanomaterial in Preparation Example 9, 12 parts of acrylic resin, 30 parts of silicone oil, 3 parts of surfactant polyethylene glycol, and 12 parts of water, place the composite conductive nanomaterial in the silicone oil, add the surfactant and the resin, stir slowly, add water during the stirring process, and mix well to obtain a curing ink functional agent.
[0072] The environmentally friendly antistatic LED-UV curing ink functional agent prepared in the above examples and comparative examples was added into conventional UV ink for testing, and the antistatic ability, adhesion and pattern printing effect of each ink were detected. The usage amount of each example and comparative example functional agent was 3-15% of the LED-UV curing ink; The formula of this conventional UV ink is as follows: 20 parts of epoxy acrylic resin monomer, 10 parts of polyester acrylic resin, 5 parts of silica, 1 part of defoaming agent, 5 parts of pentaerythritol, 20 parts of tripropylene glycol diacrylate, 5 parts of benzophenone and the environmentally friendly antistatic LED-UV curing ink functional agent in this application. The amount of the environmentally friendly antistatic LED-UV curing ink functional agent is shown in Tables 1 and 2 below.
[0073] Experiments and data The test method is as follows: The antistatic ability is tested according to the standard of GB1410-2006.
[0074] Adhesion was tested according to ASTM D3359-B.
[0075] The pattern printing effect is checked visually, with the standard being whether the pattern is clear and the color is uniform.
[0076] The test data of the embodiment are shown in Table 1 below:
[0077] The test data of the comparative example is shown in Table 2 below:
[0078] The surface resistivity of each embodiment and each comparative example is plotted as a bar graph. Figure 1 As shown, Figure 1 The value of the vertical axis is the surface resistivity 10 x The value of x in .
[0079] analyze From Table 1 and Figure 1 It can be seen from the data that the antistatic LED-UV curing ink functional agent prepared in Examples 1 to 4 has a good improvement on the surface resistivity, adhesion and printing effect of UV ink.
[0080] The antistatic LED-UV curing ink functional agent of Preparation Example 5 was used in the ink of Comparative Example 1. The carbon nanotubes of the functional agent were not plasma etched, and the remaining steps were the same as those of Preparation Example 1. According to the data in Tables 1 and 2, the surface resistivity of the oil film of Comparative Example 1 was not as good as that of Example 1, and the adhesion and printing effect decreased significantly after the increase in usage, indicating that etching the carbon nanotubes can effectively improve the adhesion of the ink on the substrate surface and the pattern printing effect.
[0081] The antistatic LED-UV curing ink functional agent of Comparative Example 2 did not perform pressurized, heated and ultrasonic treatment on the carbon nanotubes, and no water clusters were formed in the carbon nanotubes. The remaining steps were basically the same as those of Preparation Example 1. According to the data in Tables 1 and 2, the surface resistivity, adhesion and printing effect of the oil film of Comparative Example 2 were not as good as those of Example 1, indicating that the presence of water clusters can better improve the performance of the combination of polyacetylene and carbon nanotubes, and can enhance the problem of decreased antistatic ability of high-concentration functional agents.
[0082] The amount of iodinated polyacetylene used in the antistatic LED-UV curing ink functional agent of Comparative Example 3 is less than that of carbon nanotubes. According to the data in Tables 1 and 2, the surface resistivity of Comparative Example 3 is higher and the printing effect is better, but the adhesion is lower, indicating that the conjugated structure of polyacetylene is more preserved and not destroyed, and has a strong antistatic ability.
[0083] Single-arm carbon nanotubes are used in the antistatic LED-UV curing ink functional agent of Comparative Example 4. According to the data in Tables 1 and 2, the surface resistivity of the comparative example is slightly improved, but its adhesion and printing effect decrease significantly with the increase in usage, indicating that multi-walled carbon nanotubes with a larger inner diameter can improve ink adhesion and printing effect, and reduce the impact of using more antistatic agents.
[0084] In the antistatic LED-UV curing ink functional agent of Comparative Example 5, the polyacetylene is not iodinated, and the conductivity of polyacetylene is not improved. The conductivity is improved only by combining polyacetylene with carbon nanotubes. According to the data in Tables 1 and 2, the surface resistance and printing effect of Comparative Example 5 are poor, but the adhesion is very good, indicating that the conductive property of polyacetylene itself has a great influence on the antistatic property of the functional agent of the present application, and can improve the antistatic ability of the ink.
[0085] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
Claims
1. An environmentally friendly antistatic LED-UV curing ink functional agent, characterized in that: The following specific ingredients are composed by weight: Composite conductive nanomaterial: 10-30 parts, resin: 6-12 parts, silicone oil: 20-40 parts, surfactant: 1-5 parts and water: 10-20 parts; The composite conductive nanomaterial is prepared by filling carbon nanotubes and iodinated polyacetylene in a weight ratio of 1:1-1.2 and then stabilizing the mixture; The preparation method of the composite conductive nanomaterial is as follows: S1, treating the carbon nanotubes with concentrated nitric acid and drying them, then plasma etching them to obtain uncapped carbon nanotubes, placing the uncapped carbon nanotubes in water and pressurizing and heating them, and drying them to obtain carbon nanotubes, wherein the inner diameter of the carbon nanotubes is 20-50 nm; S2, placing polyacetylene in iodine vapor for reaction to obtain iodinated polyacetylene; S3, self-assembly of iodinated polyacetylene and carbon nanotubes, dissolving iodinated polyacetylene in a solvent, adding a surfactant, then adding carbon nanotubes to stir and react, and after evaporating the solvent, obtaining composite conductive nanotubes; S4. placing the composite conductive nanotubes in chloroform, adding iron powder for ultrasonic mixing treatment, and then obtaining a stabilized composite conductive nanomaterial through thermal reaction.
2. The environmentally friendly antistatic LED-UV curing ink functional agent according to claim 1, characterized in that: The carbon nanotubes in S1 are multi-walled carbon nanotubes, the diameter of the multi-walled carbon nanotubes is 30-80nm, the ratio of the carbon nanotubes to water is 1:2, the treatment pressure is 1.5-3.0MPa, the treatment temperature is 140-220°C, and the pressurized and heated treatment is followed by ultrasonic treatment, the ultrasonic power is 200-300w, and the ultrasonic treatment time is 20-30min.
3. The environmentally friendly antistatic LED-UV curing ink functional agent according to claim 1, characterized in that: The mass ratio of the polyacetylene to the iodine vapor is 1:2-3, and the reaction temperature is 190-220°C.
4. The environmentally friendly antistatic LED-UV curing ink functional agent according to claim 1, characterized in that: The S3 solvent is one of n-octane, chloroform, chloroform or tetrahydrofuran, and the solid-liquid ratio of the iodinated polyacetylene to the solvent is 1g:100-120ml.
5. The environmentally friendly antistatic LED-UV curing ink functional agent according to claim 1, characterized in that: The surfactant in S3 is one of sodium dodecyl sulfate, sodium dodecyl sulfonate, sodium tetrapropylene benzene sulfonate or sodium diisooctyl sulfosuccinate.
6. The environmentally friendly antistatic LED-UV curing ink functional agent according to claim 1, characterized in that: The added volume ratio of the surfactant to the solvent in the S3 is 2-10:
100.
7. The environmentally friendly antistatic LED-UV curing ink functional agent according to claim 1, characterized in that: The solid-liquid ratio of the carbon nanotubes in S1 treated with concentrated nitric acid is 1g:10ml, the treatment temperature is 140-200°C, and the reaction time is 24-48h.
8. The environmentally friendly antistatic LED-UV curing ink functional agent according to claim 1, characterized in that: In the S1, the plasma excitation power of the plasma etching is 100-2000W, the etching environment pressure is 1000Pa, and the impact gas of the plasma etching is one of oxygen, air, nitrogen or argon.
9. The environmentally friendly antistatic LED-UV curing ink functional agent according to claim 1, characterized in that: The usage amount of the functional agent is 3-15% of the LED-UV curing ink.
10. Use of an environmentally friendly antistatic LED-UV curing ink functional agent according to any one of claims 1 to 9 in ink.
Citation Information
Patent Citations
Printable antistatic emulsion with strong adhesive force, preparation method, antistatic film and film preparation method
CN115975497A
WATER-BASED ANTISTATIC PRIMER AND PROCESS FOR PAINTING ELECTRICALLY INSULATING SUBSTRATES
FR3078341A1
Antistatic film and method for manufacturing the same
JP2009208366A
High-dispersion carbon nanotube composite conductive ink
US20170029646A1
Antistatic powder coating and preparation method therefor
WO2022134568A1